Formação compartilhada do(a) professor(a) engenheiro(a) e educação ciência, tecnologia e sociedade no contexto do Instituto Federal de Minas Gerais - Silva, Ricardo de Lima (2023)
This thesis was developed within the scope of Professional Technological Education (EPT) and was carried out in the context of a Shared Training Group (GFC), which is made up of educational techniques and engineering professors from the Federal Institute of Education, Science and Technology of Minas Gerais (IFMG), campus Betim. It aims to understand the effects of a shared training action, verifying the convergences, divergences and challenges that are shown in the training of the engineer teacher in the face of assumptions guided by CTS Education. Qualitative in nature, it assumes research-training as a theoretical-methodological perspective and begins through the bibliographic investigation of hypotheses and guidelines that allow understanding the training of engineer teachers. In the theoretical aspect, it had contributions from Walter Antônio Bazzo, Antônio Nóvoa, Francisco Imbernón and Maria do Céu Roldão. The production of data from the conversation circles used instruments such as audio recording and textual transcription (WARSCHAUER, 2017). The analytical and interpretative process in Discursive Textual Analysis (DTA) was performed with a coded spreadsheet and showed four initial categories and one emerging category, with 53 descriptive statements (DEs) and 133 observations (MORAES; GALIAZZI, 2006). In the “Engineer teacher education” axis, the categories of analysis were constituted: “The importance and challenges for the engineer teacher education” and “Discussions and articulations for professional development”. In the “Education Science, Technology and Society (STS)” axis, we highlight the categories: “Conceptions and understandings about science, technology and society and their interrelationships” and “Links between STS Education and Engineering Education” and as a category emerging: “Participation and collectivity”. The interpretations show that the individual and collective movements in the shared training action contributed to important understandings about fundamental dimensions of the training of the engineer teacher, such as: democratization and creation of new spaces-times of teacher training, humanization, sharing and experiential learning, valuing of professional teaching knowledge, critical and reflective training, contextualization and interdisciplinarity, diversity and identity processes. It presents seven central arguments and a unifying argument for the final thesis and a proposal for the continuity of the shared training action. From the understandings and interpretations, we communicate the emergence of the thesis: to assume the action of shared formation as a singular/plural movement of research-formation in a privileged locus of understanding of the social and historical processes of the formation of the Engineer Teacher (a) enables a critical, reflective, humanizing and participatory posture in a two-way street for the opening of Education in Engineering to the public space of education through STS Education. Faced with this recursive training movement, we understand that it is possible to aim for greater sharing of experiences, humanization of practice and strengthening of professional and social participation, with greater collective awareness of responsibilities in relation to the ongoing civilizing process, given the urgency of defining an equation that maximize human dignity, or at least contribute to the reduction of inequalities.